2023
DOI: 10.1073/pnas.2300281120
|View full text |Cite
|
Sign up to set email alerts
|

The optimized Fenton-like activity of Fe single-atom sites by Fe atomic clusters–mediated electronic configuration modulation

Abstract: The performance optimization of isolated atomically dispersed metal active sites is critical but challenging. Here, TiO 2 @Fe species-N-C catalysts with Fe atomic clusters (ACs) and satellite Fe-N 4 active sites were fabricated to initiate peroxymonosulfate (PMS) oxidation reaction. The AC-induced charge redistribution of single atoms (SAs) was verified, thus strengthening the interaction between SAs and PMS. In detail, the incorporation of ACs optimized the HSO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(23 citation statements)
references
References 50 publications
1
22
0
Order By: Relevance
“…At a particle size of 0.7 nm (equivalent to 19 Pt atoms), the farthest interaction distance observed was 0.8 nm, while at a larger particle size of 0.9 nm (27 Pt atoms), the distance increased to 1.5 nm (Figure S9). This long-range interaction has been proposed by several research groups. …”
Section: Resultsmentioning
confidence: 93%
“…At a particle size of 0.7 nm (equivalent to 19 Pt atoms), the farthest interaction distance observed was 0.8 nm, while at a larger particle size of 0.9 nm (27 Pt atoms), the distance increased to 1.5 nm (Figure S9). This long-range interaction has been proposed by several research groups. …”
Section: Resultsmentioning
confidence: 93%
“…Raman spectrum showed that the ratio of I D / I G was determined as 1.01 for Co@NCNT (Figure h), whereas it increased to 1.04 and 1.07 for g-C 3 N 4 and Co@NCNS, respectively (Figure S10). This demonstrated that Co@NCNT exhibited more sp 2 sites and a higher graphitization degree than g-C 3 N 4 and Co@NCNS . Additionally, the EPR signal of Co@NCNT was obviously strengthened (Figure i), indicating its higher concentration of unpaired electrons .…”
Section: Resultsmentioning
confidence: 90%
“…This demonstrated that Co@NCNT exhibited more sp 2 sites and a higher graphitization degree than g-C 3 N 4 and Co@ NCNS. 34 Additionally, the EPR signal of Co@NCNT was obviously strengthened (Figure 2i), indicating its higher concentration of unpaired electrons. 35 The above physicochemical properties may confer greater electrical conductivity and adsorption capacity of Co@NCNT for chlorobenzene molecules through π−π interactions.…”
Section: Morphology and Structure Of The Catalystsmentioning
confidence: 97%
“…Generally, electron transfer drives the catalytic reaction process, accompanied by the generation of reactive oxygen species (ROS) . Electron transfer exists in the conversion process between different valence states of elements, especially in metal elements as active centers. The existence of the electron transfer process was verified by a cytochrome C (Cyt C, a common electron transporter) oxidization experiment. Generally, the UV–vis spectrum of Cyt C at a reduced state alone has two absorption peaks at 520 and 550 nm, and a new peak at 530 nm was able to appear once Cyt C was oxidized.…”
Section: Resultsmentioning
confidence: 99%